Strategic Ambidexterity Learning of Innovation Activities: A Study of Indonesian Business Group Leader - Retno Kusumastuti; Azhar Kasim; Sudarsono Hardjosoekarto (Indonesian Association for Public Administration, 2018)
Competitive advantage refers to the attributes an organization maintains to better perform in comparison to its competitors. According to the Resource Based View, human capital has become a source of competitive advantage. Literatures exploring how strategic leadership leads to ambidexterity practice is still very rare. Ambidexterity practices is about how organizations learn to conduct innovation activities in both exploitative and explorative manner. A prominent leader should have influence on innovation activities in their organization through the decisions they have made. This study analyzed how a corporation had implemented ambidexterity learning practices to create competitive advantage based on the leader’s cognitive map. A leader’s cognitive map is a mental construct that represents the way the leader thinks in order to deal with the prevailing environment. The dynamics of the cognitive leader is portrayed by conversing the entrepreneur’s cognitive map using the Normalized Unit Modeling by Elementary Relationship (NUMBER). This research was conducted with Lippo Karawaci (LPKR) serving as the object of study. LPKR’s success is without a doubt inseparable from the role of its leader. The results of this research show that learning process and ongoing participation based on culture to pursue competitive advantage in ambidexterity practices had occurred in LPKR. Furthermore, this study shows the importance of strategic orientation in ambidexterity learning process through proper management of the company’s resources. The identified strategic directions—human resource, technology, profitability, and entrepreneurship— may be considered as sources of competitive advantage. This research is of significant value as it presents how a big corporation, such as LPKR, constantly creates new opportunities through exploratory and exploitative innovations and learning process simultaneously thereby becoming an ambidextrous organization.